Analysis of Employee Performance Seen from Leadership Style and Work Environment as Well as Job Satisfaction as Intervening Variables - Delika Ramadhani Mnzen; Tri Bodroastuti; Lita Apriani Rustian (The Eastasouth Management and Business, 2023)
The purpose of this study was to analyze the effect of leadership style and work environment on employee performance with job satisfaction as an intervening variable. This study is a type of quantitative. The population in this study were all employees in the administration division at Disdukcapil Pati. The sample used in this study were 44 respondents using the saturated sample method. The data from this study were taken from the results of distributing questionnaires to respondents. Data Analysis techniques using statistical method by partial least squares (pls). The result obtained leadership style has a positive and significant effect on employee performance variables. Work environment has a positive and significant effect on employee performance variables. Leadership style has a positive and significant effect on the variables of job satisfaction. Work environment has a positive and significant effect on the variable job satisfaction. Employee performance has a positive and significant effect on the variable of job satisfaction.